Interferon γ: a master cytokine in microglia-mediated neural network dysfunction and neurodegeneration - Kann, Oliver; Almouhanna, Fadi; Chausse de Freitas, Bruno (Trends in neurosciences, 2022)
Traditionally, lymphocytic interferon γ (IFN-γ) was considered to be a simple 'booster' of proinflammatory responses by microglia (brain-resident macrophages) during bacterial or viral infection. Recent slice culture (in situ) and in vivo studies suggest, however, that IFN-γ has a unique role in microglial activation. Priming by IFN-γ results in proliferation (microgliosis), enhanced synapse elimination, and moderate nitric oxide release sufficient to impair synaptic transmission, gamma rhythm activity, and cognitive functions. Moreover, IFN-γ is pivotal for driving Toll-like receptor (TLR)-activated microglia into neurotoxic phenotypes that induce energetic and oxidative stress, severe network dysfunction, and neuronal death. Pharmacological targeting of activated microglia could be beneficial during elevated IFN-γ levels, blood-brain barrier leakage, and parenchymal T lymphocyte infiltration associated with, for instance, encephalitis, multiple sclerosis, and Alzheimer's disease.
Version vom 15. November 2022
Gesehen am 17.01.2023